Protective Materials and Technologies Special topic volume with invited peer-reviewed papers only - Ionescu, Mihail; Chandra, Tara; Sommitsch, Christof; Shabadi, Raj (Materials Science Forum, 2023)
The special issue is dedicated to an analysis of the recent achievements in the design and applications of protective coatings and technologies of working surface treatment and will be helpful to engineers whose activity is related to the protection and provision of engineering durability of machine parts and equipment. Steel, Alloy, Coating, Corrosion Protection, Plasma Spraying, Shot-Peening, Mechanical Properties, Electroplating, Surface Quality, Passive Shielding, Composite, Radiation Protection Materials Science, Manufacturing.